Synthesis and decarboxylation Of 2-(4-Methoxylphenyl)-1-Methyl-4,5-Dioxo-Pyrollidine-3-Carboxylic Acid Ethyl Ester / Islaili Ulfah Yaakob - Yaakob, Islaili Ulfah (Faculty of Applied Sciences, 2009)
The main focus of this experiment was synthesizing 2,3-dioxopyrrolidine for the first part. There were three main reagents to achieve the first part of this experiment. The reagents were diethyl oxalate, methyl amine and aldehyde groups. The two different aldehyde groups used were anisaldehyde and benzaldehyde. The structures of the 2,3-dioxopyrrolidine were determined using NMR. The second part of this experiment is decarboxylation. Each product from the first part underwent reflux for 2 hours in 10% HCl. The mixture obtained from decarboxylation was extracted with dicholomethane and ethyl acetate. The mixture then evaporated under reduced pressure.